The story of Science: Newton at the Center - Joy Hakim (Smithsonian Books, 2005)
Traces the period between Copernicus's theory about the sun's location at the center of the universe through the early days of atomic theory, offering introductory portraits of such contributors as Giordano Bruno, Galileo, and Isaac Newton.